Experimental Design to Assess the Existence of Chakras - Sadi, John (Journal of Scientific Exploration, 2023)
The existence of the chakras and their associated energy field is admitted by oriental tradition but has never been scientifically and convincingly demonstrated. After showing the weaknesses of past attempts toward this goal, the author describes preliminary experiments which enable to better specify the behavior of the chakra energy field. From these empirical results, a new experimental protocol is carefully designed and proposed, along with the relevant statistical analysis. The main experiment detailed here relies on randomly generated trials monitored by a computer to ensure that the double-blind criterion is met.